MENGGALI SINERGI KATEKESE DAN PASTORAL: IMPLIKASI PRAKTEK PERDUKUNAN DAN MAGI DALAM KEHIDUPAN KEAGAMAAN SUKU MALIND-ANIM DI STASI SANTO ANTONIUS KAISA - Wonmut, Xaverius; Gaol, Erly Lumban; Sedo, Raimundus (Jurnal Masalah Pastoral, 2025)
This study aims to explore the synergy between catechesis and pastoral ministry in the context of how shamanism and magic practices affect the religious life of the Malind-Anim tribe in St. Antonius Kaisa Station, St. Peter and Paul Parish, Archdiocese of Merauke. The method used is descriptive qualitative research with ethnographic and grounded theory methods. Data were collected through participatory observation, in-depth interviews with religious leaders, traditional leaders, and members of the Malind-Anim community. Data analysis was conducted thematically with a focus on how the implications of shamanism and magic practices shape the dynamics of faith and community participation. The findings show that shamanism and magic practices are still an integral part of the traditional belief system that influences the religious life of the Malind-Anim tribe. The synergy of contextual catechesis and pastoral care provides a space for dialogue and integration of Catholic values with local wisdom, thus opening up opportunities for spiritual renewal without neglecting cultural identity. In addition, adaptive pastoral strategies and dialogical catechesis are effective solutions in facing the challenges of inculturation. The practical implications of this research suggest that a humanistic and contextual catechetical-pastoral approach can strengthen the involvement of the Malind-Anim people in church life while respecting their cultural heritage.